Fenomena Living Hadis Dalam Pembelajaran Anak Usia Dini - Luthfi Maulana; Muhammad Arif Rasyid Ridha; Andi Murni (UIN Sunan Gunung Djati Bandung, 2020)
This simple research is about to study about a phenomenon of living hadith which is used as a model of learning in early childhood. The focus of this study is how the process and the occurrence of living hadith in a learning. This simple study is a field study, related to the phenomenon of living hadith. This research is descriptive, qualitative, inductive which means a research done to get a general picture or description of living hadith. The approach used in this research is phenomenology approach. The result of this simple study concludes that the model of Hadith base study conducted by Yayasan Insan Rabbani is a model of living hadith phenomenon. In addition, there are several cornerstones of hadith that serve as learning patterns and principles in building the character of children. In addition, there is a unique and interesting model, where the methods of memorization, learning, and play that are associated with the hadith, become a style in learning.